The Use of English in Empowering Micro, Small, and Medium Enterprises (MSMES) in Southeast Sulawesi - Nurunnisaa Alimah (Universitas Muhammadiyah Makassar, 2025)
English proficiency has become a pivotal skill for the growth and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Southeast Sulawesi, especially in the context of accelerating digitalization and the ongoing recovery from the COVID-19 pandemic. Indonesia is home to approximately 66 million MSMEs, which account for 61% of the national Gross Domestic Product (GDP) and employ over 97% of the country’s labor force. Despite their significant economic role, only around 26% of these enterprises have embraced digital platforms, limiting their potential to reach broader markets and engage in cross-border commerce. A major contributing factor to this digital lag is the low level of English language proficiency among business owners, which impedes their ability to create multilingual content, respond to international customers, and navigate global trade opportunities. This paper examines the strategic role of English literacy in empowering MSMEs through improved digital communication, enhanced marketing capabilities, and greater access to international networks. Drawing on recent studies, field observations, and stakeholder interviews, the paper identifies key barriers to English adoption and proposes actionable solutions, including tailored business English training and the integration of language education within entrepreneurial support programs. The study underscores the need for a holistic approach that combines language acquisition with digital literacy and capacity building to equip MSMEs for sustainable global engagement.